Total Knee Replacement for Extreme Valgus Deformity: Early Outcome in six Consecutive Cases - Ayekoloye, Charles; Oladiran, Ajibola Babatunde; Omololu, Ajibade Babatunde; Alonge, Temitope Olusegun; Ogunlade, Samuel Olusegun; Adeoye-Sunday, Imonichie I.; Okunola, Michael Oluyinka; Anejukwo, Abraham Ajimzo (Nigerian Journal of Orthopaedics and Trauma, 2020)
Introduction: About 10%–15% of patients who present for total knee replacement (TKR) present with valgus knee deformity. Valgus angulation above 20° is regarded as severe deformity. The aim of this study is to present our initial experience of the surgical management of six consecutive cases with extreme valgus deformity, highlighting surgical techniques and level of constraint required as well as clinical outcome. Patients and Methods: Six consecutive patients with end‑stage osteoarthritis and extreme valgus underwent TKR between 2016 and 2020. Demographic information, radiographic assessment and operative details were documented. Difficulties encountered and techniques used to achieve correction of deformity during surgery were detailed. Post‑operative assessment includes Oxford Knee Score (OKS) and patient satisfaction score. Results: All patients were females. The mean age was 71.8 (range: 67–82). Four patients had pie‑crusting release and valgus‑varus constraint (VVC), one had posterior stabilised implant and one a rotating‑hinge (RH) implant. Complications include one recurrent valgus instability, one partial peroneal nerve palsy treated with drop foot splint and one early post‑operative infection which resolved with treatment. The mean post‑operative follow‑up was 14.2 months (range: 3–48 months). OKS improved from a mean pre‑operative score of 18 (range: 15–21) to post‑operative mean score of 44 (range: 41–46) at a mean 14.8‑month follow‑up. All patients rated their results as satisfactory. Conclusion: Our results show that satisfactory correction of deformity and balance can be achieved, but higher levels of implant constraint were required. Long‑term follow‑up is necessary to ensure that function remains satisfactory.